2014
DOI: 10.1002/app.40964
|View full text |Cite
|
Sign up to set email alerts
|

Improving the cleanability of melamine‐formaldehyde‐based decorative laminates

Abstract: Decorative laminates based on melamine formaldehyde (MF) resin impregnated papers are used at great extent for surface finishing of engineered wood that is used for furniture, kitchen, and working surfaces, flooring and exterior cladding. In all these applications, optically flawless appearance is a major issue. The work described here is focused on enhancing the cleanability and antifingerprint properties of smooth, matt surface‐finished melamine‐coated particleboards for furniture fronts, without at the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Consequently, the technological features studied are mainly focused on mechanical strength and hydrolytic stability of the resulting boards. In contrast, impregnation resins are much less well characterized and despite their economic importance only few studies are found focusing on the technological profile important for paper impregnation 29–33 and surface coating 8,23,34–36 . The present article intends to fill this gap to some extent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the technological features studied are mainly focused on mechanical strength and hydrolytic stability of the resulting boards. In contrast, impregnation resins are much less well characterized and despite their economic importance only few studies are found focusing on the technological profile important for paper impregnation 29–33 and surface coating 8,23,34–36 . The present article intends to fill this gap to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their excellent resistance against temperature, chemicals, hydrolysis and mechanical stress, MF resins have a broad range of industrial applications. The largest application area for MF glues is in the engineered wood manufacturing industry, where they are used as adhesives for gluing wood‐based panels like particleboards and for surface finishing of such panels via resin impregnated paper laminates 1–8 …”
Section: Introductionmentioning
confidence: 99%
“…The improvements of hydrophobicity may be caused by two reasons. (1) During the curing process, the SiO bonds with lower surface free energy in the APTES tended to aggregate on the surface . The aggregation of SiO bonds was proved by XPS, the Si element content of the surface of MF‐Si material was much higher than that of the bulk, the results could be seen in Figure and Table .…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of triazine rings, MF materials are usually rigid and of weak toughness . Hydrophobicity and water resistance of MF materials are also poor because of containing abundant hydrophilic groups, such as methylol (CH 2 OH) . Employing formaldehyde as its raw material, the emission of hazardous formaldehyde is inevitable…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation